Effects of repeated abobotulinumtoxinA injections in upper limb spasticity. Issue 2 (13th August 2017) - Gracies, Jean‐Michel; O'Dell, Michael; Vecchio, Michele; Hedera, Peter; Kocer, Serdar; Rudzinska‐Bar, Monika; Rubin, Bruce; Timerbaeva, Sofiya L.; Lusakowska, Anna; Boyer, François Constant; Grandoulier, Anne‐Sophie; Vilain, Claire; et al.
ABSTRACT: Introduction : The efficacy of single injections of abobotulinumtoxinA (Dysport) is established in adults with upper limb spasticity. In this study we assessed the effects of repeated injections of abobotulinumtoxinA over 1 year. Methods : Patients ( n = 258, safety population) received 500 U, 1, 000 U, or 1, 500 U (1, 500‐U dose included 500‐U shoulder injections) for up to 4 or 5 treatment cycles. Assessments included treatment‐emergent adverse events (TEAEs), muscle tone, passive and active range of motion (XV1, XA ), angle of catch (XV3 ), Disability Assessment Scale (DAS) score, Modified Frenchay Scale (MFS) score, and Physician Global Assessment (PGA) score. Results : The incidence of TEAEs decreased across cycles. Muscle tone reduction and XV1 remained stable across cycles, whereas XV3 and XA continued to improve at the finger, wrist, and elbow flexors. DAS and PGA improved across cycles. MFS improved best with 1, 500 U. Discussion : A favorable safety profile and continuous improvements in active movements and perceived and active function were associated with repeated abobotulinumtoxinA injections in upper limb muscles. Muscle Nerve 57 : 245–254, 2018